EFEKTIFITAS PIJAT REFLEKSI TERHADAP BUANG AIR BESAR (BAB) PADA PASIEN POST OPERASI SECTIO CAESAREA DENGAN ANESTESI SPINAL DI RUANG CAMAR I RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Lita Riduan; Satria Jalu Saputra (Jurnal Keperawatan Abdurrab, 2019)
ABSTRACT The difficultness of defecation is most problems happend to post surgical operation of sectio caesarea patients. It is because of anesthesia premedication. One of the solutions is reflexology massage therapy. The aim of this research was to knowed the effectiveness of reflexology massage therapy post surgical operation to defecation of sectio caesarea patients with spinal anestetion at camar I Arifin achmad public hospital pekanbaru. Pra eksperimental is used in this research. Consecutive sampling method is used in this research with the amount of sample was 30 respondens post surgical operation of sectio caesarea patient with spinal anestetion at Camar I. Univariate analisys is used whith distribution frequency, bivariate analisys is used independent sample t test. The result of research show p value 0,027. Reflexology massage therapy had effectiveness to fastness defecation to post surgical sectio caesarea patients. From this research reflexology massage therapy can be an intervention to risk of constipation problem for post surgical sectio caesarea patients in Arifin Achmad Public Hospital Pekanbaru.